Penerapan Sanksi Administrasi Kepada Wajib Pajak Orang Pribadi - Zanzibar; Dicky Armanda; Hadi Iskandar (Asia-Pacific Journal of Public Policy, 2021)
This study aims to identify the effectiveness of implementing administrative sanctions toward personal tax income at the Tax Office in Aceh province. A qualitative method was applied in collecting the data through observation, semi-structured in-depth interviews, and document analysis. The finding reported that most taxpayers in the city did not submit their reports honestly and appropriately. They did not register to become taxpayers when the income earned has exceeded the lower limit of income following Law Number 36 of 2008 concerning Income Tax. Besides, the number of addresses of taxpayers is incomplete or incorrect, making it difficult for officers to visit their homes or offices. Invalid Taxpayer Identity also makes it difficult for officers to send Tax Bill (STP) to taxpayers. To realize the implementation of administrative sanctions operating efficiently, the community (taxpayer) is required to understand the purpose and benefits of taxes. The citizen needs to realize that the tax will be used by the government to build infrastructures for the city and develop social prosperity and well-being through improving health, nutrition, education, and social services.